DILEMA PEMANFAATAN TANAH ULAYAT UNTUK INVESTASI DI SUMATERA BARAT PADA NORMA DAN IMPLEMENTASI - Zefrizal Nurdin (Jurnal Media Hukum, 2015)
The Communal Right to Land (Hak Ulayat), both as the economic source and communal identity, should be empowered and be protected. This research studies the regulation of the utilization of Tanah Ulayat for the interest of investment and finds the root of its conflict in West Sumatera.  The result of the research concludes that there is no both horizontal and vertical synchronization in regulating of Tanah Ulayat. The regulations that have been enacted by DPRD and governor of West Sumatera are not in line with the Adat and Custom of Adat Community. Those regulations are also far from an ideal regulation and Syariah (Islamic Law), while the root of the conflict is the inconsistence between the regulation of Tanah Ulayat and its implementation which ignore the contract